Uporaba računalniško podprte procesne tehnike za integracijo industrijskih procesov - Tokos, Hella (visokošolska dela, 2009)
Process integration is an efficient tool which enables the reduction of freshwater as well as heat and electricity consumption in existing plants according to the principles of sustainable development. Computer aided processengineering tools together with mathematical programming enable systematic and simultaneous handling of process integration problems. However,mathematical models often need several modifications in large-scale industrial applications in order to suit the specific needs of industrial environment. Models need to be adjusted for existing processes in order to generate useful results for the company. This thesis is focused on reduction of three most important resources, water, heat and electricity. Besides, the sustainability indices are evaluated. In the case of freshwater reduction, the mixed integer nonlinear programming (MINLP) model developed by Kim and Smith (2004), for design of discontinuous water systems was taken as the origin for mathematical modelling. The original formulation was upgraded within this dissertation in order to be applied to the study problem. The following options were included in the model: a) water re-use between continuous and batch processes, b) installation of storage tanks for unused continuous wastewater streams in order to be re-used in subsequent time intervals when the continuous processes are shut down, and c) installation of local treatment units at the production site. Upgraded model enables selectionbetween batch and continuous local treatment units. It performs scheduling of batch treatment unit by simultaneously adjusting treatment schedule to the fixed schedule of batch production. A sequential multilevel strategy was proposed for integrating several water systems and designing the total water network. This strategy relies on the developed models and was applied to the integration of production and filling sections in the case studied brewery. In the case of heat integration, the mixed integer programming (MILP) model by Lee and Reklaitis, 1995, was applied as the basic mathematical formulation for heat integration and scheduling of cyclic batch processes. This formulation was modified in three segments: a) processes without temperature changes were included in the model besides hot and cold streams, b) streams splitting and multiple matches between streams were allowed, and c) economic objective function was defined instead of relative utility savings as in the basic formulation. The modified mathematical model was tested in the brewhouse of the case studied brewery. Polygeneration is an effective technology for combined production of mechanical or electrical, thermal and cooling energy using the same primary energy source, which enablesremarkable energy savings. MILP mathematical model was developed for the case studied brewery in order to perform feasibility studies of several polygeneration systems and select the optimal one. The superstructure includescogeneration and trigeneration systems with back-pressure steam turbine, and cogeneration system with gas turbine. Companies follow the environmental, social and economic indicators, and the composite index of sustainable development in order to improve their control of sustainable performance. For this reason, the impact of process integration results on selected sustainability indicators and the composite index was evaluated besides the economical effects. By realizing the proposed process integrationsolutions, the brewery could reduce its specific water consumption by 25 %, and specific heat consumption by 3,2 %. Installation of cogeneration system with back-pressure steam turbine would reduce the electricity purchase cost by 42 %, and CO2 emission by 45 %. All projects are economically viable, moreover, the composite index of sustainable development would improve by 2 %.
Keywords: Disertacije; električna energija; Industrijski procesi; Integracija; kontinuirni procesi; poligeneracija; retrofit; šaržni procesi; toplota; vodni sistemi